Economic analysis of endovascular drug-eluting treatments for femoropopliteal artery disease in the UK. Issue 5 (9th May 2016) - Katsanos, Konstantinos; Geisler, Benjamin P; Garner, Abigail M; Zayed, Hany; Cleveland, Trevor; Pietzsch, Jan B
Abstract : Objectives: To estimate the clinical and economic impact of drug-eluting endovascular treatment strategies for femoropopliteal artery disease compared with current standard of care. Design: Systematic literature search to pool target lesion revascularisations (TLR). Model-based per-patient cost impact and quasi-cost-effectiveness projection over 24 months based on pooled TLRs and current reimbursement. Setting: The UK's National Health Service (NHS). Participants: Patients presenting with symptomatic femoropopliteal disease eligible for endovascular treatment. Interventions: Current National Institute for Health and Care Excellence (NICE) guideline-recommended treatment with percutaneous transluminal balloon angioplasty (PTA) and bailout bare metal stenting (BMS) versus primary BMS placement, or drug-coated balloon (DCB), or drug-eluting stent (DES) treatment. Primary and secondary outcome measures: 24-month per-patient cost impact to NHS (primary outcome). Secondary outcomes: pooled 24-month TLR rates; numbers needed to treat (NNTs); cost per TLR avoided and estimated incremental cost-effectiveness ratio (ICER) in £ per quality-adjusted life year (QALY). Results: N=28 studies were identified, reporting on 5167 femoropopliteal lesions. Over 24 months, DCB, DES and BMS reduced TLRs of de novo lesions from 36.2% to 17.6%, 19.4% and 26.9%, respectively, at an increased cost of £43, £44 and £112. NNTs to avoid 1 TLR in 24 months were 5.4, 6.0 and 10.8, resulting in cost per TLR avoided of £231, £264 and £1204. DCB was estimated to add 0.011 QALYs, DES 0.010 QALYs and BMS 0.005 QALYs, resulting in estimated ICERs of £3983, £4534 and £20 719 per QALY gained. A subset analysis revealed more favourable clinical and economic outcomes for a 3.5 µg/mm 2 DCB with urea excipient, compared with the rest of DCBs. A modest reduction of 10% in DCB and DES prices made drug-eluting treatments dominant. Conclusions: Widespread adoption of drug-eluting endovascular therapies for femoropopliteal disease would add meaningful clinical benefit at reasonable additional costs to the NHS. Based on currently available data, DCBs offer the highest clinical and economic value.